Association between health insurance coverage and uptake of seasonal influenza vaccine in Brazos County, Texas. Issue 9 (24th February 2020) - Akpalu, Yao; Sullivan, Seth J.; Regan, Annette K.
Highlights: Although vaccination offers protection against influenza, 34% of individuals receive an influenza vaccine each year. Limited health insurance may contribute to low vaccination rates, particularly in areas with lower insurance coverage. Among residents of Brazos County who had influenza in December 2017, 38% did not have health insurance. Only 19% of those without health insurance had influenza vaccination compared to 30% of insured individuals. Making influenza vaccine more readily accessible to the uninsured should be an objective of public health practice. Abstract: Background: Lack of health insurance may limit access to influenza vaccination, resulting in higher risk of infection. Methods: The Brazos County Health Department obtained medical records summarizing vaccination and health insurance status of all influenza cases occurring in December 2017 (n = 417). The odds of influenza vaccination were estimated for those with public or private health insurance as compared to uninsured individuals using multivariate logistic regression analysis adjusted for age and race. Results: Health insurance coverage among Brazos County residents with influenza was 62.4%. Public and private health insurance was associated with higher odds of influenza vaccination compared to no insurance (aOR: 2.05; 95% CI: 1.00–4.21 and aOR: 1.77; 95% CI: 1.07–2.92, respectively), particularly among adults 18–64 years of age. Conclusions: Influenza vaccination is strongly associated with health insurance. Expansion of programs that facilitate access to health services or provide free influenza vaccines may improve influenza prevention among the uninsured.